Journal of the Geological Society of India - Mahabaleswar, B.; SpringerLink (Online service) (New Delhi : Geological Society of India : Imprint: Springer.)
The Journal aims to promote the cause of advanced study and research in all branches of geology connected with India, and to disseminate the findings of geological research in India through the publication.
Keywords: Geology; Hydrogeology; Geology; Hydrogeology